Effect of Pluchea Indica on glucose consumption of chang liver cells - Suriyah, Wastuti; Taher, Muhammad; Ichwan, Solachuddin J. A.; Kasmuri, Abdul Razak (2013)
Diabetes mellitus is a chronic metabolic disorder that has reached epidernic proportions with the estimated prevalence rates and trends are escalating largely in developing countries. Medicinal plants have been used as an option to treat diabeterand its complications. Our previous in vitro study has revealed that P. indica extracts stimulated insulin secretion in pancreatic beta cells and increased glucose uptake in adipocytes. The present study was aimed to observe the activity of P. indica extracts in the stimulation of glucose consumption in Chang liver cells (CCL-13) as the model of hepatocytes analyzed by glucose oxidation method. P. indica leaves were extracted in a series of organic solvents (n-hexane, dichloromethane, ethylr acetate, and methanol) and water. The maximum tolerated concentration of the extracts was ditemrined based on the MTT assay at 0.2 mg/ml. We found that methanol extract significantly elevated glucose consumption in Chang liver cells (p30.05). This result indicated tlat tne extract was useful in enhancing glucose uptake into liver cells under basal state. Further study will be focused on the expression of genes involved in the glucose uptake induced by the extract